BEYOND THE BOOK STACKS: THE ROAD MAP OF THE PHILIPPINE LIBRARY PROFESSION - Ramos, Mila M.; Ananoria, Arabella M.; Nera, Corazon M. (Journal of Philippine Librarianship; Vol 34 (2014), 2015)
Filipino professionals must brace themselves for the implementation of the ASEAN mutual agreement on borderless delivery of goods and services among member countries in 2015. As an initial step towards global competitiveness, the Professional Regulation Commission (PRC) tasked each of the forty six (46) Professional Regulatory Boards to prepare Road maps for their respective professions. The Road map embodies the vision and mission of each profession, the status and current roles of professionals, the major issues and challenges, and the action agenda to overcome the challenges.